Hybrid electric propulsion systems for skydiving aircraft - Glassock, Richard; Galea, Michael; Williams, Warren; Glesk, Tibor (2017)
• Show viability of hybrid electric and all-electric aircraft concept for skydiving missions. • Push forward, investment in new electrical propulsion technology equipped light commuter category aircraft.